Особенности контроля и отладки мпс на различных этапах жизненного цикла - Комаровский, В. Э. (ХНУРЕ, 2019)
The feature of control and debugging of microprocessor are examined on three stages of life cycle, such as design manufacturing and exploitation. The specific of every stage is taken into account. On every stage, microprocessor can have some defect and specialist analyzes and eliminates it by using special tool. This article is a brief overview of concepts for microprocessor debugging